Effect of Dietary Paeoniae Radix Alba Extract on the Growth Performance, Nutrient Digestibility and Metabolism, Serum Biochemistry, and Small Intestine Histomorphology of Raccoon Dog During the Growing Period - Wang, Jing; Li, Guangyu; Zhong, Wei; Zhang, Haihua; Yang, Qianlong; Chen, Lihong; Wang, Jinming; Yang, Xuewen (Frontiers in Veterinary Science, 2022)
Paeoniae radix alba extract (PRA extract) has the functions of regulating immunity, resisting inflammation, and has antioxidant properties. However, current recommendations of dietary PRA extract levels for raccoon dogs were inadequate. The purpose of this experimental study was to gain information allowing for better estimating the effects of PRA extract on raccoon dogs, and their PRA requirements. Fifty healthy male raccoon dogs of (120 ± 5) days old were randomly divided into 5 groups (group PRA0, PRA1, PRA2, PRA4, PRA8) with 10 animals in each group and 1 in each replicate. Five kinds of experimental diets were prepared with five levels of Paeoniae radix alba extract (0, 1, 2, 4, 8 g/kg) in the basic diet. The prefeeding period was 7 days and the experimental period was 40 days. The results showed that the average daily feed intake in group PRA1 and PRA2 was significantly higher than that in other groups (P < 0.01). The dry matter excretion in group PRA8 was significantly higher than that in other groups (P < 0.01), while the dry matter digestibility and protein digestibility in group PRA8 were significantly lower than those in other groups (P < 0.01). Nitrogen retention in group PRA1 and PRA2 was significantly higher than that in group PRA8 (P < 0.05). With the increase of the content of Paeoniae radix alba extract in diet, the activity of alkaline phosphatase in group PRA2 was significantly higher than that in group PRA0 (P < 0.05); The activity of serum SOD in group PRA4 was significantly higher than that in other groups (P < 0.01). The content of serum IgA in group PRA2 was significantly higher than that in other groups (P < 0.05). The content of TNF-α in intestinal mucosa in group PRA1 and group PRA2 was significantly lower than that in group PRA0 (P < 0.05). In conclusion, we found that dietary Paeoniae radix alba extract intake significantly improved the feed intake and nitrogen deposition of Ussuri raccoon dog, increased the content of serum IgA and reduced the content of TNF-α in the small intestinal mucosa. We suggest that an estimated dietary Paeoniae radix alba extract level of 1 to 2 g/kg could be used as a guide to achieve the optimal performance of raccoon dogs.